(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
The theoretical and legal foundations of property taxation of legal entities, its mechanism and methodology are analyzed. The study shows the role of the average annual value and cadastral value methods in calculating the property tax base in current legislation. The advantages and disadvantages of each approach are identified, and scientific proposals are developed to improve the taxation system. Existing problems in assessing the economic and legal aspects of taxation and their solutions are considered.